The Impact of Nutritional Fingerprint on Energy Production and Performance Enhancement in Wrestling Athlete - Khothier, Ghazwan (Journal of Physical Education, 2025)
The purpose of this study was to determine the effects of personalized nutrition approach by genotype based on genetic profiling and their effects on the components of energy production and performance in wrestling. The investigation concerns with five wrestlers from Al-Kadhimiyah wrestling Club, for the 74 kg weight category. During 4 weeks, each of these athletes received a diet training intervention tailored to their individual genetic profiling. Aerobic capacity (VO2max), anaerobic power (Wingate Anaerobic Test), RSA, and lower body strength (1RM squat) were assessed at baseline and post-intervention as well. Results In all variables significant improvements were observed with VO2max increasing by 5 ml/kg/min, both peak and mean power output by 50 and 25 watts respectively and fatigue index reduced by 6.5%. Furthermore, strength levels of all participants increased, with an average 15 kg increase in 1RM squat strength. These results indicate that individualized nutrition based on genomics can greatly improve athletic performance, especially for high-intensity sports such as wrestling, which require endurance, power and strength.